Circadian Variation and Baseline Definition in Parallel-Group Thorough QT Studies. (March 2014) - Hoffman, David
For thorough QT (TQT) studies employing a parallel-group design, there has been a clear regulatory preference for the use of time-matched, rather than time-averaged, baseline values to account for circadian variation when estimating the magnitude of the drug effect on the QT interval. In this paper, both historical data from parallel-group TQT studies and simulated data from assumed circadian models are utilized to comprehensively assess the performance characteristics of 3 repeated-measures analysis of covariance models. The results indicate that each analysis model performs adequately in the absence of an observed time-matched baseline imbalance between the treatment groups. However, the analysis model with time-matched baseline as a covariate performs poorly under the setting of an observed time-matched baseline imbalance between the treatment groups. The analysis model with time-averaged baseline as a covariate and the analysis model with both time-matched and time-averaged baselines as covariates provide unbiased estimates of the treatment difference and properly control the type I error rate, regardless of an observed time-matched baseline imbalance or within-patient variation in circadian parameters.